Patient stratification and choice of therapy based on blood gene expression profiles in rheumatoid arthritis - E. V. Chetina; G. A. Markova (Современная ревматология)
Rheumatoid arthritis (RA) is a chronic inflammatory disease of unknown etiology, in which different parts of the immune system and other tissues are involved and joint destruction also occurs. Current therapy methods are aimed at suppressing inflammation and reducing pain; however, they do not affect the pathophysiological and biochemical mechanisms involved in joint destruction. Moreover, RA patients are an exclusively heterogeneous group, so not all of them respond equally well to treatment. In this regard, there is a need for personalized therapy. However, the patient's assessment, including clinical, immunological, and radiological parameters, does not currently allow the response to anti-rheumatic treatment to be predicted in about half of the cases. Just the same, recent studies suggest that patient stratification according to the blood level of proinflammatory genes can help predict a response to antirheumatic therapy.